THE ROLE OF LEADERSHIP IN IMPROVING WORK DISCIPLINE OF CIVIL SERVANTS POLICE UNIT OF THE CENTRAL BUTON REGENCY - Husnah Katjina (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to determine the role of leadership in improving the work discipline of employees of the Civil Service Police Unit of Buton Tengah Regency. The population in this study was 143 Civil Service Police Unit employees, while the sample in this study was 4 employees of the Civil Service Police Unit of Buton Tengah Regency. Data collection used interview, observation, and documentation techniques. The data analysis methods used were triangulation, data reduction, and data presentation. The results of the study indicate that the leadership in the Civil Service Police Unit of Buton Tengah Regency has been very good in carrying out its role in improving employee discipline, namely by always providing instructions and motivation to employees, providing coaching to employees, and providing sanctions in accordance with applicable regulations, namely PP. 53 of 2010 on employee work discipline and regulations issued by the Regent of Buton Tengah Regency. In improving employee discipline, the leadership conducts supervision in the form of supervision using the E-Sipja application and conducting monthly attendance evaluations. Punishment sanctions appropriate to the level of violation include a mild verbal warning and a moderate suspension of promotion. The firmness of the sanctions and strong leadership have led to positive changes in the Civil Service Police Unit, which have significantly improved work discipline for all employees.